2023
DOI: 10.1037/pag0000735
|View full text |Cite
|
Sign up to set email alerts
|

Age-related differences in the statistical learning of target selection and distractor suppression.

Abstract: In recent years, the use of implicit mechanisms based on statistical learning (SL) has emerged as a strong factor in biasing visuospatial attention, so that target selection is improved at frequently attended locations and distractor filtering is facilitated at frequently suppressed locations. Although these mechanisms have been consistently described in younger adults, similar evidence in healthy aging is scarce. Therefore, we studied the learning and persistence of SL of target selection and distractor suppr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(5 citation statements)
references
References 94 publications
(184 reference statements)
2
1
0
Order By: Relevance
“…Finally, we identified that deficiencies in selection history, specifically intertrial priming, do not explain why older adults show slowing in performance. This finding is consistent with the aging literature that selection history effects are preserved in older adults over different attention tasks (Howard Jr. et al, 2004;Lega et al, 2023;Lyon et al, 2014;Smyth & Shanks, 2011).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Finally, we identified that deficiencies in selection history, specifically intertrial priming, do not explain why older adults show slowing in performance. This finding is consistent with the aging literature that selection history effects are preserved in older adults over different attention tasks (Howard Jr. et al, 2004;Lega et al, 2023;Lyon et al, 2014;Smyth & Shanks, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings that top-down processing is delayed, and that early proactive inhibition is preserved in older adults would also support this notion. However, there are some studies that conclude that proactive distractor suppression is impaired in older adults (Ashinoff et al, 2019(Ashinoff et al, , 2020Lega et al, 2023;Lustig & Jantz, 2015). Furthermore, Ashinoff et al (2020) suggests that older adults shift from proactive inhibitory processing to reactive control in a global/local task.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, we identified that deficiencies in selection history, specifically intertrial priming, do not explain why older adults show slowing in performance. This finding is consistent with the aging literature that selection history effects are preserved in older adults over different attention tasks (Howard et al, 2004; Lega et al, 2023; Lyon et al, 2014; Smyth & Shanks, 2011).…”
Section: Discussionsupporting
confidence: 92%
“…Our findings that top-down processing is delayed, and that early proactive inhibition is preserved in older adults would also support this notion. However, there are some studies that conclude that proactive distractor suppression is impaired in older adults (Ashinoff et al, 2019(Ashinoff et al, , 2020Lega et al, 2023;Lustig & Jantz, 2015). Furthermore, Ashinoff et al (2020) suggest that older adults shift from proactive inhibitory processing to reactive control in a global/local task.…”
Section: Discussionmentioning
confidence: 99%
“…The authors found that older adults maintain preserved mechanisms of orienting during feature search and exhibit impaired goal-directed attentional control with the alerting cue as seen in the Attention Network Test, in addition to being significantly distracted by the salient distractor as in the aging and inhibition literature. Furthermore, older adults displayed age equivalence in mechanisms of selection history as previously observed (Howard Jr. et al, 2004; Lega et al, 2023; Lyon et al, 2014; Smyth & Shanks, 2011) and interestingly, could inhibit the salient distractor when the task design required proactive suppression. Although significant advances have been made to understand how aging affects mechanisms of attentional control, the neurobiological bases of why specific networks of attention are affected and why others remain unaltered is yet unknown.…”
Section: Introductionsupporting
confidence: 72%